Anionic surfactants based on intermediates of carbohydrate conversion. Issue 14 (26th June 2019) - Kipshagen, Lukas; Vömel, Lukas T.; Liauw, Marcel A.; Klemmer, Anna; Schulz, Alexander; Kropf, Christian; Hausoul, Peter J. C.; Palkovits, Regina
Abstract : Starting from the bio-based platform chemicals 5-hydroxymethylfurfural (HMF) and furfural, a library of anionic surfactants was synthesized using stoichiometric and catalytic reactions. Abstract : Starting from the bio-based platform chemicals 5-hydroxymethylfurfural (HMF) and furfural, a library of anionic surfactants was synthesized using stoichiometric and catalytic reactions. In total, seven different surfactants with varying chain lengths were prepared and tested for industrially relevant properties, such as critical micelle concentration (CMC) and interfacial tension towards isopropyl myristate. Surfactants based on 2, 5-bis(hydroxymethyl)-tetrahydrofuran (BHMTHF), which are accessible via acid-catalysis over zeolites, were identified as the most promising candidates for possible industrial applications. Variants with chain lengths of C12 –C14 showed the best results in terms of physico-chemical properties. These lengths represent the usually occurring length of carbon chains in natural oils, opening up a pathway for a possible production of the here used substrates. The other synthesized surfactants, accessible via stoichiometric routes, also showed promising results in terms of CMC and interfacial tension.